Vagal reactivation after a cardiac rehabilitation session associated with hydration in coronary artery disease patients: crossover clinical trial - Laurino, Maria Júlia Lopez [UNESP]; da Silva, Anne Kastelianne França [UNESP]; Santos, Lorena Altafin [UNESP]; Ribeiro, Felipe [UNESP]; Vanzella, Laís Manata [UNESP]; Corazza, Dayane Andrade Genoni [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Springer Nature, 2021)
This study aimed to investigate the hydration influence on the autonomic responses of coronary artery disease subjects in the immediate recovery period after a cardiovascular rehabilitation session, in view of the risks of a delayed autonomic recovery for this population. 28 males with coronary artery disease were submitted to: (I) Maximum effort test; (II) Control protocol (CP), composed by initial rest, warm-up, exercise and passive recovery; (III) Hydration protocol (HP) similar to CP, but with rehydration during exercise. The recovery was evaluated through the heart rate (HR) variability, HR recovery and by the rate of perceived exertion and recovery. The main results revealed that the vagal reactivation occurred at the first 30 s of recovery in HP and after the first minute in CP. A better behavior of the HR at the first minute of recovery was observed in HP. The rate of perceived exertion had a significant decrease in the first minute of recovery in HP, while in CP this occurred after the third minute. In conclusion, despite an anticipated vagal reactivation found at HP, these results should be analyzed with caution as there were no significant differences between protocols for all variables and the effect sizes were small.